Letter - Roberts, Wilfrid
1940-05-14 038-0041-001 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMAN: THE EARL OF LISTOWEL MISS ELEANOR RATHBONE, M.P. HON. SECRETARIES: Mr. D.R. GRENFELL, M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. WILFRID ROBERTS, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING & APPEALS SECRETARY: Mrs. V.E. MILLER 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 May 14th. 1940 At a joint meeting of the National Joint Committee for Spanish Relief, the Basque Children's Committee and the British Committee for Refugees from Spain held on Friday May 3rd. it was unanimously agreed that the work of the Committees would be more efficiently carried on under present circumstances if a Joint Executive was appointed to act for the three Committees. It is not proposed to dissolve the existing Committees, but in future they will only be summoned when a substantial number of members of any one of the Committees concerned ask for a meeting of that Committee alone. It was further agreed that the names of those to act on the Joint Executive should be selected from those members who had recently attended meetings regularly. The following are the names suggested. Further names may be added if members of the Committees concerned so desire. Yours sincerely, p.p. Wilfrid Roberts. V.M. Hon. Secretary. 292/946/38/41(I)